Measurement of vibrations induced by high-speed trains - Martins, João Paulo (2009)
The paper describes the preliminary test campaign carried out in the national research project POCI/ECM/61114/2004, entitled “Interaction soil-railway track for high speed trains”, in Portugal. In this context, a preliminary measurement test campaign with vibration sensors was performed in the Portuguese North Railway Line. The next project task will be the instrumentation of several sections with different geometric and geotechnical characteristics. Therefore, the paper present aspects related to testing equipment, the testing and results discussion, including the signal processing. The measurement results will be also used to calibrate numerical models.